2014
DOI: 10.15298/rusjtheriol.13.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and cytogenetic variation of African root-rats Tachyoryctes splendens (Mammalia: Rodentia) from Ethiopia

Abstract: Genetic and cytogenetic variation of African root-rats Tachyoryctes splendens sensu lato from Ethiopia was assessed on 23 complete cytochrome b gene sequences (1140 bp) and chromosomal sets from eight individuals. Results of this study suggest that the real diversity of Ethiopian Tachyoryctes splendens s.l. has been underestimated due to its apparent cryptic diversification. The molecular genetic analysis reveals genetic subdivision including at least four allopatric and deeply divergent mitochondrial lineages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…These two forms were recognised as only two root-rat species (Beolchini & Corti 2004, Kingdon et al 2013, Wilson et al 2017, but some authors split T. splendens into more than 10 species (Ellerman 1941, Musser & Carleton 2005, Monadjem et al 2015. Recently, Lavrenchenko et al (2014) found high mitochondrial diversity in T. splendens in Ethiopia. Later, Šumbera et al (2018) extended the geographic sampling and number of genetic markers from the preceding study.…”
Section: Subfamily Rhizomyinae Tribe Tachyoryctinimentioning
confidence: 99%
See 2 more Smart Citations
“…These two forms were recognised as only two root-rat species (Beolchini & Corti 2004, Kingdon et al 2013, Wilson et al 2017, but some authors split T. splendens into more than 10 species (Ellerman 1941, Musser & Carleton 2005, Monadjem et al 2015. Recently, Lavrenchenko et al (2014) found high mitochondrial diversity in T. splendens in Ethiopia. Later, Šumbera et al (2018) extended the geographic sampling and number of genetic markers from the preceding study.…”
Section: Subfamily Rhizomyinae Tribe Tachyoryctinimentioning
confidence: 99%
“…foraging on the surface while having their hind legs still in the burrow (L. Lavrenchenko, unpublished data). There are two distinct karyotypes 2n = 48, FN = 58; 2n = 50, FN = 58 (Lavrenchenko et al 2014).…”
Section: Gerbillus Dunnimentioning
confidence: 99%
See 1 more Smart Citation
“…The process of adaptation to an underground lifestyle can lead to a decreasing of the level of dispersion of animals and, as a consequence, to decreasing of the effective population size [14]. This creates the conditions for the appearance of the chromosomal variation, and it is among underground rodents that there are examples of the existence of a wide range of karyotypic diversity (for example, genera Ctenomys, Thomomys, Spalax, Ellobius, Tachyoryctes) [15][16][17]. It is worth noting that the further evolutionary "step"-the transition from the existing polymorphism to divergence and, as a result, to the process of speciation-is still practically unexplored [18].…”
Section: Short Communicationsmentioning
confidence: 99%
“…These unique environmental conditions have encouraged intensive speciation processes, making the Ethiopian plateau a "mammal diversity hotspot", i.e. a centre of diversification for numerous Ethiopian mammal taxa (Lavrenchenko et al 2004(Lavrenchenko et al , 2007(Lavrenchenko et al , 2014. Ethiopia is characterised by a high degree of endemism, with 36 mammalian species presently considered endemic to the country (Bekele and Yalden 2013).…”
Section: Introductionmentioning
confidence: 99%